2016
DOI: 10.1039/c5cp05260b
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the nanoclay induced constrained amorphous region in model segmented polyurethane–urea/clay nanocomposites and its implications on gas barrier properties

Abstract: There has been an increasing recognition of the fact that purely geometric factors associated with clay platelet dispersion in a polymer matrix cannot adequately explain the barrier properties of polymer/clay nanocomposites. The objective of the present work is to understand the nanoclay induced structural changes in a polyurethane-urea matrix and clay dispersion at different length scales using segment-specific characterization techniques and implications of the same in gas barrier properties using He, N2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Nanoclay could be seen as dark coloured aggregates. The AFM micrograph showed that the clay agglomerates were broken into smaller tactoids, which are then intercalated/ exfoliated in HTPB [42,43].…”
Section: Resultsmentioning
confidence: 99%
“…Nanoclay could be seen as dark coloured aggregates. The AFM micrograph showed that the clay agglomerates were broken into smaller tactoids, which are then intercalated/ exfoliated in HTPB [42,43].…”
Section: Resultsmentioning
confidence: 99%
“…According to experimental results, a reduction in the segmental mobility of the chains near the surface of each lamina is observed due to the incorporation of organoclay. Therefore, the chain polymer rests immobilized, modifying significantly the physical properties .…”
Section: Introductionmentioning
confidence: 99%
“…38,39 This technique involves mapping the spatial variation of specific elements by rastering the electron beam over an area of interest. 38 From the EDS spectra, pertaining to the Zr elemental maps of the nanocomposites (Figure 3), it is observed that at 10% α-ZrP loading, the nanofiller distribution is uniform and homogenous with no evidence of agglomeration of the nanofiller. At higher loadings, agglomeration is evident with agglomerate sizes in the range 2−4 μm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%